CZY EUROPEJSKA KONWENCJA PRAW CZŁOWIEKA JAKO „ŻYWY INSTRUMENT” CHRONI LEPIEJ LUDZKIE ŻYCIE? - Joanna Banasiuk (Zeszyty Prawnicze)
IS THE EUROPEAN CONVENTION ON HUMAN RIGHTS TREATED AS A “LIVING INSTRUMENT” AFFORDING BETTER PROTECTION OF HUMAN LIFE? Summary The Strasbourg Court appears to be using the provisions of the European Convention on Human Rights in a free way to shape the content of legal norms. The purpose of this article is to exemplify this controversial process by the judgement of 30th October 2012 in P. and S. v. Poland, which, as some commentators have already observed, appears to be tending to the construction of a right to abortion alleging Article 8 of the Convention considered completely out of the context of the guarantees for the protection of human life in Article 2. The judgement shows that the Court treated the case as based on grounds resulting from rape, but no evidence was produced to corroborate these grounds. This is confirmed by the lack of consistency between the particular formulations of the judgement. Furthermore, the way in which the facts were presented, on which the Court based its judgement, is not in agreement with the content of the documents produced as evidence by Poland. The Court left a series of points of evidence unexamined, and raised unwarranted reservations on the action the doctors had taken in compliance with Polish law. In effect the European Court of Human Rights treated the same course of action which it had deemed necessary in the proceedings of V.C. v. Slovakia, and N.B. v Slovakia as a violation of Articles 3 and 8 of the ECHR in the case of P. and S. v. Poland. This fact seems to raise a serious issue regarding the interpretation or application of the Convention in the context of the material.